POS12 Telemedicine is as safe as bedside delivery for thrombolysis in acute stroke. Issue 11 (22nd October 2010) - Pollock, S; Munro, N; Hargroves, D; Manjunathan, S; Pullicino, P; Karlsson, J; Gunathilagan, G; Burger, I; Baht, H; Pollock, S; Ogburn, W; Thomas, G
Abstract : Introduction: Intravenous thrombolysis is a target within the national stroke strategy but there are insufficient specialists to provide a 24-h bedside service for all UK hospitals. Thrombolysis in the 3 EKHUFT acute hospitals, (population 730 000), is undertaken in-hours at the bedside and out-of-hours remotely by a single rota of five stroke physicians and four neurologists. We report the first year results comparing bedside and telemedicine safety outcomes. Method: From September 2008, prospective data were analysed from stroke thrombolysis calls initiated via the EKHUFT switchboard. Retrospective correlation from hospital notes, PACS images and coded discharge episodes. Results: 836 patients were admitted with a diagnosis of ischaemic stroke (ICD 163*). 103 (12.3%) received intravenous thrombolysis, 61% by telemedicine; mean admission NIHSS: 11.3. Mortality, at 15.2% was lower than 20% SITS data and did not vary significantly between the two groups (Abstract POS12 Table 1 ). Conclusion: Telemedicine is as safe as bedside thrombolysis. It permits remote decision making and the safe use of intravenous thrombolysis at multiple sites with one rota. It may obviate the need for hyper acute stroke units, reducing transfer times and repatriation problems.